2018
DOI: 10.1038/s41598-018-33047-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological conditions drive pace-of-life syndromes by shaping relationships between life history, physiology and behaviour in two populations of Eastern mosquitofish

Abstract: The pace-of-life syndrome (POLS) hypothesis predicts variation in behaviour and physiology among individuals to be associated with variation in life history. Thus, individuals on the “fast” end of POLS continuum grow faster, exhibit higher metabolism, are more risk prone, but die earlier than ones on the “slow” end. Empirical support is nevertheless mixed and modelling studies suggested POLS to vary along selection gradients. Therefore, including ecological variation when testing POLS is vastly needed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 66 publications
(116 reference statements)
4
77
0
Order By: Relevance
“…Our work underscores that the predictions of the pace‐of‐life hypothesis with respect to personality and life history correlations can be context dependent and can vary among ecological conditions, thereby complicating generalizations (Polverino et al. ; Royauté et al. ; Wright et al.…”
Section: Discussionmentioning
confidence: 90%
“…Our work underscores that the predictions of the pace‐of‐life hypothesis with respect to personality and life history correlations can be context dependent and can vary among ecological conditions, thereby complicating generalizations (Polverino et al. ; Royauté et al. ; Wright et al.…”
Section: Discussionmentioning
confidence: 90%
“…The effects of predictability or stochasticity of the environment on POLS has not been directly addressed, but some evidence indicates a potential for unpredictability to contribute to the effects of an unfavourable environment. Polverino, Santostefano, Díaz-Gil, & Mehner (2018) found distinctly different POLS-trait covariance structures in lab-reared mosquitofish that originated from a stable (possibly more favourable) habitat, relative to fish from a harsher, unpredictable source habitat. While the study supports the hypothesis in that POLS was found only under the more predictable environment, the direction of the trait correlations were opposite to those predicted: the fish sourced from the more predictable environment expressed a slower POL relative to fish from the unpredictable habitat, but their slower POL was associated with higher metabolic maintenance costs, higher activity and boldness.…”
Section: Current Evidence For H2mentioning
confidence: 86%
“…In fact, we demonstrated an adaptive behavioral link between boldness and daily activity rhythms in the small-, but not in the large-, harvested line. Fisheries-induced evolution of behavior likely has a complex and multivariate nature (9, 21), thereby complicating generalizations related to evolutionary correlations among traits (45-47). The somewhat asymmetrical adaptation of behavior in the two size-selection lines did not extend to all traits that we measured, which could be related to a functional limitation of the range of evolution of our model species (21, 48).…”
Section: Discussionmentioning
confidence: 99%